ECONOMIC AND SOCIAL ASPECTS OF URBAN AGRICULTURE IN LATVIA – A CASE STUDY - Dobele, Madara (Journal of Regional Economic and Social Development, 2022)
Urban agriculture is developing rapidly in the world, paying significant, often primary attention not only to the economic but also to the social and environmental functions of the practice. Urban agriculture in Latvia is relatively underdeveloped, most of the practice is realized in small amounts in households for self-consumption. Similarly, evaluating produced volumes and results in the context of commercial practice and community and public projects, it is in a developmental stage. Urban agriculture in Latvia has also been little researched so far, and the practice does not have a specific legal status that would enable precise determination of the scope of the practice, financial and trend analysis. However, the practice is developing, especially in the form of community gardens. The aim of this study is to determine and describe economic and social aspects of urban agriculture in Latvia. In order to achieve the aim, a systematic theoretical review was used to determine the definition and boundaries of the practice of urban agriculture, analysis and synthesis methods were used to identify and characterize trends, and a case study was used to summarize the economic and social aspects of the practice specific to Latvia. Results of the research confirm that social aspects dominate in urban agriculture in Latvia - in aims, motivation, functions and advantages of the practice. But in terms of risks, the most important are economic aspects, which are also the main hindering factors in the development of urban agriculture in Latvia.